The Prevalence & Proportion of Haematological Complications of Malaria in a Tertiary Care Hospital - Riaz A. Qazi, S. Qaiser H. Naqvi, M. Shiraz Khan, Rasool Bux Shalkh, Anwar A. Akhund , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2011)
Objectives:- To find out the prevalence and hematological complications of malaria in a tertiary care hospital. Study design:- Descriptive and observational study Place and Duration:- This study was conducted at Out Patients Departments of PUMHS Hospital (OPD) and Pathology Department of Peoples University of Medical and Health Sciences Nawabshah from April 2011 to September 2011. Patients and methods:- A total 1230 cases of malaria diagnosed on basis of clinical and laboratory findings were recorded. The proportion ofhaemotological complication including anaemia, leucocytosis and thrombocytopenia among these patients were also studied. Results:- Out of 1230 patients, 720 (58.3%) were children and remaining 510 (41.7) were adults. Ages of these patients including children and adults ranged between 5 to 65 years with a mean of 35 ± 30. Male to female ratio in these patients were 1.4:1. The diagnosis of malaria was made by clinical and confirmed by laboratory findings. The problem of haematological complications as anaemia, leucocytosis and thrombocytopenia were detected among the patient with malaria by determination of Haemoglobin concentration and Complete Blood Count (CBC). Conclusion:- P.Vivax Malaria is more prevalent. While many of these patient are children and women. Anaemia, leucocytosis and thrombocytopenia are common haematological complications in them.